2022
DOI: 10.1111/apt.17162
|View full text |Cite
|
Sign up to set email alerts
|

Increasing rates of venous thromboembolism among hospitalised patients with inflammatory bowel disease: a nationwide analysis

Abstract: Summary Background Venous thromboembolism (VTE) is a significant cause of morbidity and mortality among patients with inflammatory bowel disease (IBD). However, data on national trends remain limited. Aims To assess national trends in VTE‐associated hospitalisations among patients with IBD as well as risk factors for, and mortality associated with, these events Methods Using the U.S. Nationwide Inpatient Sample from 2000–2018, temporal trends in VTE were assessed using the National Cancer Institute's Joinpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
0
16
0
2
Order By: Relevance
“…72 73 Systemic corticosteroids were associated with significantly higher rate of VTE complications in IBD patients compared with IBD patient without steroid medication (OR: 1.22; 95% CI: 1.16–1.29). 8 Corticosteroids can induce hypercoagulability, by increasing plasma fibrinogen level and decreasing tPA activity and prostacyclin synthesis. 74 Furthermore, the use of corticosteroids before hospitalization is an independent risk for VTE.…”
Section: Risk Factors For Vte In Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…72 73 Systemic corticosteroids were associated with significantly higher rate of VTE complications in IBD patients compared with IBD patient without steroid medication (OR: 1.22; 95% CI: 1.16–1.29). 8 Corticosteroids can induce hypercoagulability, by increasing plasma fibrinogen level and decreasing tPA activity and prostacyclin synthesis. 74 Furthermore, the use of corticosteroids before hospitalization is an independent risk for VTE.…”
Section: Risk Factors For Vte In Ibdmentioning
confidence: 99%
“…The incidence of VTE increases with age, and it is associated with active disease (defined as corticosteroid use) and hospitalization. 2 Although most studies found no significant sex-related differences in VTE incidence, it was recently reported that male sex may be associated with an increased risk of VTE-related hospitalization [6][7][8] ; the extent of the disease may also correlate with a higher VTE risk. 9 A retrospective study found pancolonic involvement in 76% of patients with UC and VTE, whereas colonic involvement, complicated disease (i.e., fistulas, stenosis, abscesses), and recent surgery were reported as risk factors for CD.…”
mentioning
confidence: 99%
“…We read with special interest the recently published work by Faye et al 1 regarding the time trends of venous thromboembolism (VTE) events in patients hospitalised for any cause with a diagnosis of inflammatory bowel disease (IBD). Their analysis, utilising the U.S. Nationwide Inpatient Sample (NIS) from 2000 to 2018, observed that 4,859,728 hospitalizations of patients with IBD included 128,236 (2.6%) having a VTE event, with 6352 associated deaths.…”
Section: Editorsmentioning
confidence: 99%
“…The authors' declarations of personal and financial interests are unchanged from those in the original article. 3…”
Section: Auth O R S H I Pmentioning
confidence: 99%